Activation and Purification of ß-Glucocerebrosidase by Exploiting its Transporter LIMP-2 – Implications for Novel Treatment Strategies in Gaucher's and Parkinson's Disease - Dobert, Jan; Bub, Simon; Mächtel, Rebecca; Januliene, Dovile; Steger, Lisa; Regensburger, Martin; Wilfling, Sibylle; Chen, Jia Xuan; Dejung, Mario; Plötz, Sonja; Hehr, Ute; Moeller, Arne; et al. (Advanced Science, 2024)
Genetic variants of GBA1 can cause the lysosomal storage disorder Gaucher disease and are among the highest genetic risk factors for Parkinson's disease (PD). GBA1 encodes the lysosomal enzyme beta-glucocerebrosidase (GCase), which orchestrates the degradation of glucosylceramide (GluCer) in the lysosome. Recent studies have shown that GluCer accelerates α-synuclein aggregation, exposing GCase deficiency as a major risk factor in PD pathology and as a promising target for treatment. This study investigates the interaction of GCase and three disease-associated variants (p.E326K, p.N370S, p.L444P) with their transporter, the lysosomal integral membrane protein 2 (LIMP-2). Overexpression of LIMP-2 in HEK 293T cells boosts lysosomal abundance of wt, E326K, and N370S GCase and increases/rescues enzymatic activity of the wt and E326K variant. Using a novel purification approach, co-purification of untagged wt, E326K, and N370S GCase in complex with His-tagged LIMP-2 from cell supernatant of HEK 293F cells is achieved, confirming functional binding and trafficking for these variants. Furthermore, a single helix in the LIMP-2 ectodomain is exploited to design a lysosome-targeted peptide that enhances lysosomal GCase activity in PD patient-derived and control fibroblasts. These findings reveal LIMP-2 as an allosteric activator of GCase, suggesting a possible therapeutic potential of targeting this interaction.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Gaucher's disease (GD); GCase; LIMP-2; lysosomes; Parkinson's disease (PD); protein purification; β-glucocerebrosidase

Cancer-Type Organic Anion Transporting Polypeptide 1B3 Is Localized in Lysosomes and Mediates Resistance against Kinase Inhibitors - Haberkorn, Bastian; Oswald, Stefan; Kehl, Niklas; Geßner, Arne; Taudte, Verena; Dobert, Jan; Zunke, Friederike; Fromm, Martin; König, Jörg (Molecular Pharmacology, 2022)
Cancer-type organic anion transporting polypeptide 1B3 (CtOATP1B3), a splice variant of the hepatic uptake transporter OATP1B3 (liver-type), is expressed in several tumor entities, including colorectal carcinoma (CRC) and breast cancer. In CRC, high OATP1B3 expression has been associated with reduced progression-free and overall survival. Several kinase inhibitors used for antitumor treatment are substrates and/or inhibitors of OATP1B3 (e.g., encorafenib, vemurafenib). The functional importance of CtOATP1B3 has not been elucidated so far. Human embryonic kidney 293 cells stably overexpressing Ct-OATP1B3 protein were established and compared with control cells. Confocal laser scanning microscopy, immunoblot, and proteomics-based expression analysis demonstrated that Ct-OATP1B3 protein is intracellularly localized in lysosomes of stably transfected cells. Cytotoxicity experiments showed that cells recombinantly expressing the Ct-OATP1B3 protein were more resistant against the kinase inhibitor encorafenib compared with control cells [e.g., encorafenib (100 mM) survival rates: 89.5% versus 52.8%]. In line with these findings, colorectal cancer DLD1 cells endogenously expressing Ct-OATP1B3 protein had poorer survival rates when the OATP1B3 substrate bromosulfophthalein (BSP) was coincubated with encorafenib or vemurafenib compared with the incubation with the kinase inhibitor alone. This indicates a competitive inhibition of Ct-OATP1B3–mediated uptake into lysosomes by BSP. Accordingly, mass spectrometry-based drug analysis of lysosomes showed a reduced lysosomal accumulation of encorafenib in DLD1 cells additionally exposed to BSP. These results demonstrate that Ct-OATP1B3 protein is localized in the lysosomal membrane and can mediate transport of certain kinase inhibitors into lysosomes, revealing a new mechanism of resistance.
Created from Fastlane, Scopus look-up

Corrigendum: Cathepsin D Variants Associated With Neurodegenerative Diseases Show Dysregulated Functionality and Modified α-Synuclein Degradation Properties (Frontiers in Cell and Developmental Biology, (2021), 9, (581805), 10.3389/fcell.2021.581805) - Bunk, Josina; Prieto Huarcaya, Susy; Drobny, Alice; Dobert, Jan; Walther, Lina; Rose-John, Stefan; Arnold, Philipp; Zunke, Friederike (Frontiers in Cell and Developmental Biology, 2021)
In the original article, there was a mistake in Figure 1C as published. In the Coomassie brilliant blue (CBB) protein staining, which was used as additional loading control (besides GAPDH), 11 instead of 10 sample lanes (+ protein ladder) were shown in the original Figure 1C. This mistake resulted from an additional sample (transfection control), that was loaded on the far right. This lane was not shown in both immunoblots (CTSD and GAPDH), but accidentally was still shown in the CBB control. The corrected Figure 1C appears below. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-16
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomes; molecular dynamics simulation; neuronal ceroid lipofuscinoses; Parkinson's disease

Cryo-TEM structure of β-glucocerebrosidase in complex with its transporter LIMP-2 - Dobert, Jan; Schäfer, Jan-Hannes; Dal Maso, Thomas; Ravindran, Priyadarshini; Huard, Dustin J. E.; Socher, Eileen; Schildmeyer, Lisa A.; Lieberman, Raquel L.; Versées, Wim; Moeller, Arne; Zunke, Friederike; Arnold, Philipp (Nature Communications, 2025)
Targeting proteins to their final cellular destination requires transport mechanisms and nearly all lysosomal enzymes reach the lysosome via the mannose-6-phosphate receptor pathway. One of the few known exceptions is the enzyme β-glucocerebrosidase (GCase) that requires the lysosomal integral membrane protein type-2 (LIMP-2) as a proprietary lysosomal transporter. Genetic variations in the GCase encoding gene GBA1 cause Gaucher’s disease (GD) and present the highest genetic risk factor to develop Parkinson’s disease (PD). Activators targeting GCase emerge as a promising therapeutic approach to treat GD and PD, with pre-clinical and clinical trials ongoing. In this study, we resolve the complex of GCase and LIMP-2 using cryo-electron microscopy with the aid of an engineered LIMP-2 shuttle and two GCase-targeted pro-macrobodies. We identify helix 5 and helix 7 of LIMP-2 to interact with a binding pocket in GCase, forming a mostly hydrophobic interaction interface supported by one essential salt bridge. Understanding the interplay of GCase and LIMP-2 on a structural level is crucial to identify potential activation sites and conceptualizing novel therapeutic approaches targeting GCase. Here, we unveil the protein structure of a mannose-6-phosphate-independent lysosomal transport complex and provide fundamental knowledge for translational clinical research to overcome GD and P
Keywords: Cryoelectron microscopy; Enzymes; Membrane proteins; Parkinson's disease

From Lysosomal Storage Disorders to Parkinson's Disease – Challenges and Opportunities - Mächtel, Rebecca; Boros, Fanni Annamaria; Dobert, Jan; Arnold, Philipp; Zunke, Friederike (Journal of Molecular Biology, 2023)
Lysosomes are specialized organelles with an acidic pH that act as recycling hubs for intracellular and extracellular components. They harbour numerous different hydrolytic enzymes to degrade substrates like proteins, peptides, and glycolipids. Reduced catalytic activity of lysosomal enzymes can cause the accumulation of these substrates and loss of lysosomal integrity, resulting in lysosomal dysfunction and lysosomal storage disorders (LSDs). Post-mitotic cells, such as neurons, seem to be highly sensitive to damages induced by lysosomal dysfunction, thus LSDs often manifest with neurological symptoms. Interestingly, some LSDs and Parkinson's disease (PD) share common cellular pathomechanisms, suggesting convergence of aetiology of the two disease types. This is further underlined by genetic associations of several lysosomal genes involved in LSDs with PD. The increasing number of lysosome-associated genetic risk factors for PD makes it necessary to understand functions and interactions of lysosomal proteins/enzymes both in health and disease, thereby holding the potential to identify new therapeutic targets. In this review, we highlight genetic and mechanistic interactions between the complex lysosomal network, LSDs and PD, and elaborate on methodical challenges in lysosomal research.
CRIS-Team Scopus Importer:2023-03-24
Keywords: lysosomal enzymes; lysosomal storage disorder; lysosome; neurodegeneration; Parkinson's disease

Late-onset Krabbe disease presenting as spastic paraplegia – implications of GCase and CTSB/D - Mächtel, Rebecca; Dobert, Jan; Hehr, Ute; Weiß, Alexander; Kettwig, Matthias; Laugwitz, Lucia; Groeschel, Samuel; Schmidt, Manuel; Arnold, Philipp; Regensburger, Martin; Zunke, Friederike (Annals of Clinical and Translational Neurology, 2024)
Objective: Krabbe disease (KD) is a multisystem neurodegenerative disorder with severe disability and premature death, mostly with an infancy/childhood onset. In rare cases of late-onset phenotypes, symptoms are often milder and difficult to diagnose. We here present a translational approach combining diagnostic and biochemical analyses of a male patient with a progressive gait disorder starting at the age of 44 years, with a final diagnosis of late-onset KD (LOKD). Methods: Additionally to cerebral MRI, protein structural analyses of the β-galactocerebrosidase protein (GALC) were performed. Moreover, expression, lysosomal localization, and activities of β-glucocerebrosidase (GCase), cathepsin B (CTSB), and cathepsin D (CTSD) were analyzed in leukocytes, fibroblasts, and lysosomes of fibroblasts. Results: Exome sequencing revealed biallelic likely pathogenic variants: GALC exons 11–17: 33 kb deletion; exon 4: missense variant (c.334A>G, p.Thr112Ala). We detected a reduced GALC activity in leukocytes and fibroblasts. While histological KD phenotypes were absent in fibroblasts, they showed a significantly decreased activities of GCase, CTSB, and CTSD in lysosomal fractions, while expression levels were unaffected. Interpretation: The presented LOKD case underlines the age-dependent appearance of a mildly pathogenic GALC variant and its interplay with other lysosomal proteins. As GALC malfunction results in reduced ceramide levels, we assume this to be causative for the here described decrease in CTSB and CTSD activity, potentially leading to diminished GCase activity. Hence, we emphasize the importance of a functional interplay between the lysosomal enzymes GALC, CTSB, CTSD, and GCase, as well as between their substrates, and propose their conjoined contribution in KD pathology.
CRIS-Team Scopus Importer:2024-06-14
Keywords: cathepsin B; cathepsin D; enzymatic activity; Krabbe disease; late-onset; β-glucocerebrosidase

Recombinant pro-CTSD (cathepsin D) enhances SNCA/α-Synuclein degradation in α-Synucleinopathy models. - Huarcaya, Alice Prieto; Drobny, Susy; Marques, Andre R. A.; Di Spiezio, Alessandro; Dobert, Jan; Balta, Denise; Werner, Christian; Rizo Garza, Tania; Gallwitz, Lisa; Bub, Simon; Stojkovska, Iva; Belur, Nandkishore R.; et al. (Autophagy, 2022)
Parkinson disease (PD) is a neurodegenerative disorder characterized by the abnormal intracellular accumulation of SNCA/α-synuclein. While the exact mechanisms underlying SNCA pathology are not fully understood, increasing evidence suggests the involvement of autophagy as well as lysosomal deficiencies. Because CTSD (cathepsin D) has been proposed to be the major lysosomal protease involved in SNCA degradation, its deficiency has been linked to the presence of insoluble SNCA conformers in the brain of mice and humans as well as to the transcellular transmission of SNCA aggregates. We here postulate that SNCA degradation can be enhanced by the application of the recombinant human proform of CTSD (rHsCTSD). Our results reveal that rHsCTSD is efficiently endocytosed by neuronal cells, correctly targeted to lysosomes and matured to an enzymatically active protease. In dopaminergic neurons derived from induced pluripotent stem cells (iPSC) of PD patients harboring the A53T mutation within the SNCA gene, we confirm the reduction of insoluble SNCA after treatment with rHsCTSD. Moreover, we demonstrate a decrease of pathological SNCA conformers in the brain and within primary neurons of a ctsd-deficient mouse model after dosing with rHsCTSD. Boosting lysosomal CTSD activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function. Our findings indicate that CTSD is critical for SNCA clearance and function. Thus, enzyme replacement strategies utilizing CTSD may also be of therapeutic interest for the treatment of PD and other synucleinopathies aiming to decrease the SNCA burden.Abbreviations: aa: amino acid; SNCA/α-synuclein: synuclein alpha; APP: amyloid beta precursor protein; BBB: blood brain barrier; BF: basal forebrain; CBB: Coomassie Brilliant Blue; CLN: neuronal ceroid lipofuscinosis; CNL10: neuronal ceroid lipofuscinosis type 10; Corr.: corrected; CTSD: cathepsin D; CTSB: cathepsin B; DA: dopaminergic; DA-iPSn: induced pluripotent stem cell-derived dopaminergic neurons; dox: doxycycline; ERT: enzyme replacement therapy; Fx: fornix, GBA/β-glucocerebrosidase: glucosylceramidase beta; h: hour; HC: hippocampus; HT: hypothalamus; i.c.: intracranially; IF: immunofluorescence; iPSC: induced pluripotent stem cell; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LSDs: lysosomal storage disorders; MAPT: microtubule associated protein tau; M6P: mannose-6-phosphate; M6PR: mannose-6-phosphate receptor; MB: midbrain; mCTSD: mature form of CTSD; neurofil.: neurofilament; PD: Parkinson disease; proCTSD: proform of CTSD; PRNP: prion protein; RFU: relative fluorescence units; rHsCTSD: recombinant human proCTSD; SAPC: Saposin C; SIM: structured illumination microscopy; T-insol: Triton-insoluble; T-sol: Triton-soluble; TEM: transmission electron microscopy, TH: tyrosine hydroxylase; Thal: thalamus.
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomal storage disorders; parkinson disease; synucleinopathies

The role of lysosomal cathepsins in neurodegeneration: Mechanistic insights, diagnostic potential and therapeutic approaches - Drobny, Alice; Prieto Huarcaya, Susy; Dobert, Jan; Kluge, Annika; Bunk, Josina; Schlothauer, Theresia; Zunke, Friederike (Biochimica Et Biophysica Acta-Molecular Cell Research, 2022)
Lysosomes are ubiquitous organelles with a fundamental role in maintaining cellular homeostasis by mediating degradation and recycling processes. Cathepsins are the most abundant lysosomal hydrolyses and are responsible for the bulk degradation of various substrates. A correct autophagic function is essential for neuronal survival, as most neurons are post-mitotic and thus susceptible to accumulate cellular components. Increasing evidence suggests a crucial role of the lysosome in neurodegeneration as a key regulator of aggregation-prone and disease-associated proteins, such as α-synuclein, β-amyloid and huntingtin. Particularly, alterations in lysosomal cathepsins CTSD, CTSB and CTSL can contribute to the pathogenesis of neurodegenerative diseases as seen for neuronal ceroid lipofuscinosis, synucleinopathies (Parkinson's disease, Dementia with Lewy Body and Multiple System Atrophy) as well as Alzheimer's and Huntington's disease. In this review, we provide an overview of recent evidence implicating CTSD, CTSB and CTSL in neurodegeneration, with a special focus on the role of these enzymes in α-synuclein metabolism. In addition, we summarize the potential role of lysosomal cathepsins as clinical biomarkers in neurodegenerative diseases and discuss potential therapeutic approaches by targeting lysosomal function.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Alzheimer's disease; Cathepsins; Huntington's disease; Lysosome; Neurodegeneration; Neuronal ceroid lipofuscinosis; Parkinson's disease; Synucleinopathies; α-Synuclein